Polarization Switching in Ferroelectric Thin Films Undergoing First-Order Phase Transitions. (17th June 2010) - Bakaleinikov, L. A.; Gordon, A.
Abstract : The main switching properties in ferroelectrics undergoing first-order phase transitions are simulated within the framework of the extended Ishibashi dipole-lattice model including the dipole-dipole interaction in a two-dimensional case for ferroelectric nanoscale objects. The peculiarities of the temperature dependence of the switching rate and the pyroelectric coefficient are discussed in the range of coexistence of the metastable states. The used coefficients of the long-range and short-range interactions between the dipoles are taken from the dielectric and structure measurements inB a T i O 3 .